Integrating AI Tools in Spanish Language Classroom: A Practical Analysis of Student Interaction, Challenges, and Pedagogical Strategies - Raj, Kaushik (Management Analytics and Social Insights, 2026)
The growing presence of Artificial Intelligence (AI) in foreign language teaching has opened up new possibilities for improved teaching methodologies and learners engagement. The paper presents a practical analysis of AI-powered tools in beginner-level Spanish language classrooms, drawn heavily from the author own classroom teaching experiences. It examines how students interact with AI-driven applications, challenges they face, and therefore strategies for its effective pedagogical integration. The study focuses at three key levels: 1) Student Interaction with AI Tools: It analyzes how learners use popular platforms such as Duolingo, ChatGPT and Google Translate for vocabulary building, grammar corrections, and conversational practice or solving a specific problem at hand, 2) Challenges and Limitations: It looks at the concerns such as too much dependence on AI-generated translations, error in automated responses, and the need for cultural and contextual nuances and 3) Pedagogical Strategies: It explores ways in which educators can integrate AI effectively to complement, rather than replace, traditional teaching methods. The classroom observations and the survey done with the learners highlighted both the benefits and the possible drawbacks of AI’s unregulated presence in language learning. The survey findings reinforced the educator’s classroom observation that while AI tools offer personalized learning experiences and instant feedback, they must be supplemented with human-led instruction. Balancing AI automation with meaningful student engagement is the key to ensure effective learning.